Advances in molecular biomarkers and liquid biopsy in gliomas. (11th November 2022) - Mathios, Dimitrios; Phallen, Jillian
Abstract: There have been significant strides toward understanding the molecular landscape of brain cancer. These advances have been focused on analyses of the tumor microenvironment and have recently expanded to include liquid biopsies to identify molecular biomarkers noninvasively. Moving from tissue to liquid-based analyses of molecular biomarkers has been challenging and currently, there are no approved noninvasive tests that are clinically useful. However, the emerging field of molecular liquid biopsy assay development in the neuro-oncology space has great potential to revolutionize the detection and monitoring of patients with brain cancer.